2005
DOI: 10.1002/marc.200400464
|View full text |Cite
|
Sign up to set email alerts
|

Ink‐Jet Microdispensing for the Formation of Gradients of Immobilised Enzyme Activity

Abstract: Summary: The integration of gradients of enzyme activity in microstructured biosensor arrays enables intrinsic on‐line quality control of biosensor performance. Multiple sensor elements with different compositions and hence varying responses for the same analyte are evaluated as a basis for improving data reliability. The formation of glucose oxidase/polymer microstructures using a piezo microdispenser and their examination by scanning electrochemical microscopy (SECM) are used to demonstrate the feasibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
0
23
0
4
Order By: Relevance
“…The results showed that inkjet technology will have great potential in the fabrication of biosensors. Turcu et al (2005) used a custommade flow-through piezoelectric inkjet microdispenser for formation of gradients on immobilized enzyme activity. Microstructures with varying immobilized glucose oxidase (GOx) activity in a polymeric hydrogel matrix were fabricated by means of sequential dispensing of the enzyme/polymer suspension on a gold coated glass.…”
Section: Piezeoelectric and Thermal Inkjet Technologies In Biomoleculmentioning
confidence: 99%
“…The results showed that inkjet technology will have great potential in the fabrication of biosensors. Turcu et al (2005) used a custommade flow-through piezoelectric inkjet microdispenser for formation of gradients on immobilized enzyme activity. Microstructures with varying immobilized glucose oxidase (GOx) activity in a polymeric hydrogel matrix were fabricated by means of sequential dispensing of the enzyme/polymer suspension on a gold coated glass.…”
Section: Piezeoelectric and Thermal Inkjet Technologies In Biomoleculmentioning
confidence: 99%
“…Printing allows for precise placement of small volumes of bioactive molecules onto materials such as paper in a simple and low-cost approach [1,2]. Deposition of enzymes by printing offers the potential to be used in a number of nanobiomanufacturing applications including diagnostics, active and intelligent packaging, and microarrays [2][3][4]. A number of enzymes in aqueous systems have been printed using an inkjet system including glucose oxidase, acetylcholinesterase, laccase, alkaline phosphatase, and horseradish peroxidase [1,[3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of enzymes by printing offers the potential to be used in a number of nanobiomanufacturing applications including diagnostics, active and intelligent packaging, and microarrays [2][3][4]. A number of enzymes in aqueous systems have been printed using an inkjet system including glucose oxidase, acetylcholinesterase, laccase, alkaline phosphatase, and horseradish peroxidase [1,[3][4][5][6][7]. Both piezoelectric and thermal inkjet printing methods have been employed for depositing liquid enzyme solutions [4,5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, in the sample-generation-tip-collection mode of SECM (Zhou et al, 1992;Martin and Unwin, 1998) localized chemical activity can be visualized conveniently based on the detection of an electroactive species (e.g., the product of an enzymatic reaction) released from the surface by its electrochemical conversion at the SECM tip (Pierce and Bard, 1993;Wittstock and Schuhmann, 1997;Strike et al, 1999;Wittstock, 2001;Kasai et al, 2002;Zhao and Wittstock, 2004). First attempts to use the spatial inhomogeneity of enzyme microstructures for extracting increased information were demonstrated recently (Gáspár et al, 2001;Turcu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%